Access to and effects of social protection on workers living with HIV and their households : an analytical report. - Rodriguez-Garcia, Rosalia (International Labour Organization, 2014)
This report which is the result of a process that included a global literature review, the development of a research methodology guide through consultation with experts, and research in four countries: Guatemala, Indonesia, Rwanda and Ukraine. It highlights the challenges faced by workers living with HIV and their households in accessing social protection programmes, examines the effects of such programmes on their lives and makes evidence-based recommendations.